Simunovich and the Defence of Truth - Buist-Catherwood, Emily (Victoria University of Wellington Law Review, 2011)
APN New Zealand Limited v Simunovich Fisheries Limited was a significant Supreme Court judgment regarding the biggest defamation claim in New Zealand’s legal history. The Court ruled that third party statements were inadmissible as evidence for a defence of truth, unless such statements could be independently proven to be true. This paper argues that objectively reliable third party statements, such as statements made by the judiciary, should be admissible as evidence for a defence of truth in certain cases. Where a defamatory meaning of reasonable grounds to suspect guilt is pleaded, rather than an allegation of actual guilt, reliable statements made by a third party can be highly relevant in proving the existence of reasonable grounds for suspicion. A high burden is already placed on defendants to negotiate technical pleading and evidential requirements in proving the defence of truth. Simunovich erects an unnecessary further obstacle that will prevent the submission of relevant and reliable evidence. This paper recommends that the Simunovich ruling on third party statements be amended to allow such particulars to be admitted in support of a defence of truth to an alleged defamatory meaning of reasonable grounds of suspicion.